Sentidos do lúdico na educação infantil: dos dispositivos institucionais aos modos de fazer. - Pinto, Georgia Albuquerque de Toledo (2009)
This research is intended to investigate how the construction of ludic senses happens for students and teachers, considering that these actors are in different enunciative positions. We start from the hypothesis that the emphasis on ludic given by the school for childhood education may be restricting the educational activity rather than enlarge it. The theoretical tools that were used to support the analysis made here were derived mainly from Brougère, concerning the understanding of ludic; from Bakhtin, aiding in the understanding of the subjects enunciative positions during the verbal interaction; and from De Certeau, to comprehend the ways of doing. To do this, we took part in three classes in a public school for children education during a school year. The analyzed corpus is derived from a qualitative research, as the approach is ethnographic, realized by the register of an activity diary and videography resources. Another methodological tool used was the interview with the teachers: six teachers from public school for children education in Fortaleza-CE and their respective classes, each consisting of 17 students, totaling 51 children. After collecting and transcribing the recorded data a microgenetic analysis was performed on the previously selected scenes of this material. In a second time, we have selected a scene from each studied group, so that through an interview, the teachers could watch and discuss the ludic characteristics of the activities proposed by them. From the interrelationship between the theory and the empirical material collected, were built two categories of analysis: the institutional mechanisms and the ways of doing. The performed analysis brings elements of the mechanisms used by both the teacher and the students, as well as of the ways of doing of each of these actors during the school scene. It was possible to observe that the ways of doing reveal the logic of action of the actors of the scene, showing that an activity is very ludic when the meaning is shared from the beginning, regardless of its context, its participants, or the way it is characterized in its planning (if it is presented as systematic or ludic). Our data point to an idealization of ludic by the pedagogical discourse, as the use of activities with such characteristics by itself guarantees the understanding of the contents by the child. The same speech that values the rise of ludic in the pedagogical practice appears to contribute to a gradual devaluation of the pedagogical.